Cat on the run in cat of death! - Blabey, Aaron ([New York, New York] : Scholastic Inc., 2023)
What happens when the world's #1 Cat Video Star gets accused of a crime she didn't commit? She becomes a cat on the run, that's what.
Publishers Weekly, July 2023
4.0
3-6
370L
Keywords: Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Humorous stories; Cats -- Fiction; Humorous comics; Funny animal comics; Graphic novels; Comics (Graphic works)